The hepatitis C cascade of care in people who inject drugs in Dar es Salaam, Tanzania - Mohamed, Zameer; Rwegasha, John; Kim, Jin U.; Shimakawa, Yusuke; Poiteau, Lila; Chevaliez, Stéphane; Bhagani, Sanjay; Taylor‐Robinson, Simon D.; Thursz, Mark R.; Mbwambo, Jessie; Lemoine, Maud (Journal of Viral Hepatitis, 2018)
Summary The World Health Organisation has recently called for hepatitis C virus (HCV) elimination and has identified people who inject drugs (PWID) as a key population to scale‐up screening and linkage to care. This study reports the cascade of care for HCV in PWID attending the largest opioid substitution treatment (OST) clinic in Dar‐es‐Salaam, Tanzania. Between February 2011 and March 2016, HCV serology for all PWID registered at the Muhimbili National Hospital OST clinic, Dar‐es‐Salaam were obtained from records. In 2015, consecutive HCV‐seropositive PWID were invited to undergo a clinical evaluation including epidemiological questionnaire, liver stiffness measurement (Fibroscan) and virological analysis (HCV RNA viral load and genotyping). During the study period, 1350 persons registered at the OST clinic: all had a HCV serology including 409 (30%) positive results. Among the HCV‐seropositive individuals, 207 (51%) were active attenders and 153 (37%) were enrolled for clinical assessment: 141 (92%) were male, median age: 38 years (IQR 34‐41), and 65 (44%) were co‐infected with HIV; 116 patients (76%) had detectable HCV RNA, with genotypes 1a (68%) and 4a (32%); 21 (17%) had clinically significant fibrosis (≥F2) and 6 (5%) had cirrhosis (F4). None were offered HCV treatment. Chronic hepatitis C among PWID enrolled in the OST centre in Dar‐es‐Salaam is frequent, but its continuum of care is insufficient; integration of HCV diagnosis and treatment should form a part of OST intervention in PWID in Tanzania.